Hierarchical Mesoporous Metal–Organic Frameworks for Enhanced CO2 Capture. Issue 43 (10th September 2015) - Mao, Yiyin; Chen, Danke; Hu, Pan; Guo, Yi; Ying, Yulong; Ying, Wen; Peng, Xinsheng
Abstract Hierarchical porous materials are promising for catalyst, separation and sorption applications. A ligand‐assisted etching process is developed for template‐free synthesis of hierarchical mesoporous MOFs as single crystals and well‐intergrown membranes at 40 °C. At 223 K, the hierarchical porous structures significantly improve the CO2 capture capacity of HKUST‐1 by more than 44 % at pressures up to 20 kPa and 13 % at 100 kPa. Even at 323 K, the enhancement of CO2 uptake is above 25 % at pressures up to 20 kPa and 7 % at 100 kPa. The mesoporous structures not only enhance the CO2 uptake capacity but also improve the diffusion and mass transportation of CO2. Similarly, well‐intergrown mesoporous HKUST‐1 membranes are synthesized, which hold the potential for film‐like porous devices. Mesoporous MOF‐5 crystals are also obtained by a similar ligand‐assisted etching process. This may provide a facile way to prepare hierarchical porous MOF single crystals and membranes for wide‐ranging applications.